Boundary Value Problems for First-Order Impulsive Functional q-Integrodifference Equations - Jessada Tariboon; Sotiris K. Ntouyas (Abstract and Applied Analysis)
We discuss the existence and uniqueness of solutions for a first-order boundary value problem for impulsive functional qk-integrodifference equations. The main results are obtained with the aid of some classical fixed point theorems. Illustrative examples are also presented.